Structural and Functional Analysis of the Human IQSEC2 S1474Qfs*133 Mutation - Yonat Israel; Aaron Lowenkamp; Michael Shokhen; Shai Netser; Shlomo Wagner; Joseph Zarowin; Shaun Orth; Veronika Borisov; Orit Lache; Nina S. Levy; Andrew P. Levy (Biomolecules)
IQSEC2 is a guanine nucleotide exchange factor that modulates synaptic transmission, the excitatory/inhibitor balance and memory consolidation. Pathogenic mutations in the IQSEC2 gene result in epilepsy, cognitive dysfunction and autism spectrum disorder. The most common de novo IQSEC2 mutation in the IQSEC2 gene, associated with a particularly severe phenotype in males as compared to other IQSEC2 mutations, is due to a frameshift mutation near the C terminus, resulting in an extension of the open reading frame [IQSEC2 S1474Qfs*133]. The objective of this study was to understand the pathophysiology of this specific IQSEC2 mutation using molecular modeling protein–protein interaction assays and a conditional transgenic mouse model of the mutation. Molecular modeling studies showed that the mutation results in the generation of a new domain that may bind ATP. The mutant IQSEC2 protein failed to interact with proteins that normally interact with IQSEC2, most notably with PSD-95. Finally, mice expressing the human mutation displayed marked developmental delays and abnormal social behavior. We conclude that diseases associated with the IQSEC2 S1474Qfs*133 may be due not only to the loss of function of IQSEC2 but also to the appearance of new detrimental activity. The conditional mouse model will allow for the identification of brain regions that are critical for IQSEC2 expression and will serve as a platform for the development of personalized therapies for this disease.